Ahkamu’l-Qoran and Qurtubi’s Understanding of Commentary - Demirci, Mehmet (Scientific Journal of Faculty of Theology, 2019)
In this article, the concept of ahkâmu’l-Qur'an which occupying an important place in the exegesis literature and the work of Qurtubî, one of the classical works written in this field, are discussed. The scope of the concept of ahkâmu’l-Qur'an has been extended by some scholars. These scholars have evaluated the verses which give direct place to practical issues. They have also considered many verses that point indirectly to the provisions in the context of ahkâmu’l-Qur'an. Qurtubî's work named al-Cami li Ahkâmi’l-Kur’an is one of the important works written in this field. In this work, where the Qur'an is interpreted from beginning to end, the subjects of ahkâm are discussed in detail. Qurtubi has made very successful judgments from the verses which are not thought to express directly in this commentary and generally based on solid evidence in these inferences.